Exceptional co-catalysts free SrTiO3 perovskite coupled CdSe nanohybrid catalyst by green pulsed laser ablation for electrochemical hydrogen evolution reaction - M.J.S. Mohamed; M.A. Gondal; M. Hassan; A.Z. Khan; A.M. Surrati; M.A. Almessiere (Chemical Engineering Journal Advances, 2022)
In this study, a facile and green PLAL technique was used to synthesize nanohybrids consisting of SrTiO3/CdSe, as efficient cathode material for electrocatalytic HER in a basic medium. Although pure SrTiO3 perovskite has poor electrocatalytic performance, but the addition of CdSe has significantly enhanced its electrocatalytic HER activity. Synergistic interactions between SrTiO3 and CdSe are critical to enhance the nanohybrid's electrocatalytic HER performance. An optimized concentration of SrTiO3/CdSe demonstrated a significant current density of -10 mA/cm2 at an overpotential of 224.2 mV, which is much better than the same current density achieved with bare SrTiO3 and CdSe alone at overpotentials of 375.9 mV and 399.4 mV, respectively. SrTiO3/CdSe nanohybrid follows intermediate hydrogen adsorption, which is explained by the Volmer-Heyrovsky step mechanism. The incorporation of CdSe into SrTiO3 improved the nanohybrid's electrocatalytic HER performance by increasing the electrochemical surface area and number of active sites, hence facilitating the electron transfer at the semiconductor-electrolyte interface.